Differential requirements for the Eps15 homology domain proteins EHD4 and EHD2 in the regulation of mammalian ciliogenesis. (17th May 2022) - Jones, Tyler; Naslavsky, Naava; Caplan, Steve
Abstract: The endocytic protein EHD1 controls primary ciliogenesis by facilitating fusion of the ciliary vesicle and by removal of CP110 from the mother centriole. EHD3, the closest EHD1 paralog, has a similar regulatory role, but initial evidence suggested that the other two more distal paralogs, EHD2 and EHD4 may be dispensable for ciliogenesis. Herein, we define a novel role for EHD4, but not EHD2, in regulating primary ciliogenesis. To better understand the mechanisms and differential functions of the EHD proteins in ciliogenesis, we first demonstrated a requirement for EHD1 ATP‐binding to promote ciliogenesis. We then identified two sequence motifs that are entirely conserved between EH domains of EHD1, EHD3 and EHD4, but display key amino acid differences within the EHD2 EH domain. Substitution of either P446 or E470 in EHD1 with the aligning S451 or W475 residues from EHD2 was sufficient to prevent rescue of ciliogenesis in EHD1‐depleted cells upon reintroduction of EHD1. Overall, our data enhance the current understanding of the EHD paralogs in ciliogenesis, demonstrate a need for ATP‐binding and identify conserved sequences in the EH domains of EHD1, EHD3 and EHD4 that regulate EHD1 binding to proteins and its ability to rescue ciliogenesis in EHD1‐depleted cells. Abstract : Herein, we define a novel role for EHD4, but not EHD2, in regulating primary ciliogenesis, and demonstrate a requirement for EHD1 ATP‐binding to promote ciliogenesis. Overall, our data enhance the current understanding of the EHD paralogs in ciliogenesis, demonstrate a need for ATP‐binding, and identify conserved sequences in the EH domains of EHD1, EHD3 and EHD4 (but not EHD2) that regulate EH‐domain binding to proteins and bestow upon EHD1 the ability to rescue ciliogenesis in EHD1‐depleted cells.